The Role of an Integrated Multidisciplinary Clinic in the Management of Patients with Cutaneous Lymphoma - Tyler, Kelly H.; Haverkos, Bradley M.; Hastings, Justin; Hu, Eileen; Philips, Ramez; Gru, Alejandro A.; Welliver, Meng Xu; Mishra, Anjali; Wong, Henry K.; Porcu, Pierluigi (Frontiers in Oncology, 2015)
The clinical benefit of a multidisciplinary clinic practice model has been well described in a variety of medical specialties and cancer types. It proves particularly valuable when an integrated team is needed to optimally manage patients with rare or complex neoplasms. However, the ideal implementation of an integrated multidisciplinary care program for translational research and education has not been well reported. Herein, we propose how a multimodality cutaneous lymphoma clinic model can optimally manage cutaneous lymphoma patients. We offer our perspective on this model as an efficient means for delivering patient care, a continuing education resource for referring physicians, a conduit for translational and clinical research, and an educational tool for medical students, house staff, and fellows.